Homocysteine in embryo culture media as a predictor of pregnancy outcome in assisted reproductive technology. (3rd March 2016) - Boyama, Burcu Aydin; Cepni, Ismail; Imamoglu, Metehan; Oncul, Mahmut; Tuten, Abdullah; Yuksel, Mehmet Aytac; Kervancioglu, Mehmet Ertan; Kaleli, Semih; Ocal, Pelin
Abstract: The aim of this study was to determine whether homocysteine (hcy) concentrations in embryo culture media correlate with pregnancy outcome in assisted reproductive technology (ART) cycles. Forty patients who underwent single embryo transfer at the infertility clinic of a tertiary care center were recruited for this case-control study. Spent embryo culture media from all patients were collected after single embryo transfer on day 3 ( n = 40). Hcy concentrations in embryo culture media were analyzed by enzyme cycling method. Patients were grouped according to the diagnosis of a clinical pregnancy. Sixteen patients were pregnant while 24 patients failed to achieve conception. Mean Hcy levels in the culture media were significantly different between the groups ( p < 0.003), as 4.58 ± 1.31 μmol/l in the non-pregnant group and 3.37 ± 0.92 μmol/l in the pregnant group. Receiver operator curve analysis for determining the diagnostic potential of Hcy for pregnancy revealed an area under the curve of 0.792 (confidence interval: 0.65–0.94; p < 0.05). A cut-off value of 3.53 μmol/l was determined with a sensitivity of 83.3%, and a specificity of 68.8%. Lower hcy levels were associated with a better chance of pregnancy and better embryo grades. Hcy may be introduced as an individual metabolomic profiling marker for embryos.